Synthesis, crystal structure, electric and magnetic properties of new UNiSi₂ splat - Molčanová, Z.; Mihalik, M.; M. Mihalik Jr.; Rajňák, M.; Zentková, M.; Huráková, M.; Kavečanský, V.; Paukov, M.; Havela, L.; Cieslar, M.; Milianchuk, K. (Физика низких температур, 2017)
We explored the crystal structure, magnetic and transport properties of UNiSi₂ material, which was prepared by rapid solidification—splat cooling. The UNiSi₂ splat is mostly single phase, the refinement of crystal structure indicated orthorhombic CeNiSi₂-type structure (space group Cmcm) with lattice parameters a = 4.0082 Å, b = 16.0813 Å and c = 4.0064 Å. Also SEM analysis revealed the morphology exhibiting dendritic grains in the matrix. TEM images indicate mixed structure formed by crystalline particles embedded into amorphous or nanocrystalline matrix. Magnetic and electrical properties of the splat resemble properties of samples, which were prepared by conventional methods, exhibiting a ferromagnetic transition at about 91 K and similar temperature dependence of resistivity. The coercive field of μ₀Hc = 2.25 T is much enhanced due to the magnetic anisotropy introduced by the sample preparation technique. Barkhausen jumps were observed on the hysteresis loop. Magnetization of the sample does not saturate in magnetic fields up to μ₀H = 18 T.